Fighting for Citizenship : Black Northerners and the Debate over Military Service in the Civil War - Taylor, Brian (Brian M.) (Civil War America (Series), 2020)
"Understanding debates over African Americans' enlistment exposes a formative moment in the development of American citizenship: black Northerners' key demand was that military service earn full American citizenship for black men and women, a term that had no precise definition prior to the Fourteenth Amendment. In articulating this demand, Taylor argues, black Northerners participated in the remaking of American citizenship itself--unquestionably one of the war's most important results"--